2016
DOI: 10.1017/s0007485316000638
|View full text |Cite
|
Sign up to set email alerts
|

Coronatin-2 from the entomopathogenic fungus Conidiobolus coronatus kills Galleria mellonella larvae and incapacitates hemocytes

Abstract: Coronatin-2, a 14.5 kDa protein, was isolated from culture filtrates of the entomopathogenic fungus Conidiobolus coronatus (Costantin) Batko (Entomophthoramycota: Entomophthorales). After LC-MS/MS (liquid chromatography tandem mass spectrometry) analysis of the tryptic peptide digest of coronatin-2 and a mass spectra database search no orthologs of this protein could be found in fungi. The highest homology was observed to the partial translation elongation factor 1a from Sphaerosporium equinum (protein sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…One such species, C. coronatus, is a soil fungus which demonstrates entomopathogenicity towards a number of insects, including G. mellonella, Dendrolimus pini [35] and various collembolans [36]. It is known to produce various mycotoxins [37,38], including a 30 kDa protein believed to be toxic to G. mellonella larvae, coronatin-1 (36 kDa) and coronatin-2 (14.5 kDa) which compromise the function of hemocytes, and the 30-32 kDa serine protease, whose properties resemble subtilisin [35,[37][38][39]. A previous study also has shown that while exposure did not influence the fat bodies, characteristic changes were observed in the Malpighian tubules in G. mellonella larvae after infection [40].…”
Section: Discussionmentioning
confidence: 99%
“…One such species, C. coronatus, is a soil fungus which demonstrates entomopathogenicity towards a number of insects, including G. mellonella, Dendrolimus pini [35] and various collembolans [36]. It is known to produce various mycotoxins [37,38], including a 30 kDa protein believed to be toxic to G. mellonella larvae, coronatin-1 (36 kDa) and coronatin-2 (14.5 kDa) which compromise the function of hemocytes, and the 30-32 kDa serine protease, whose properties resemble subtilisin [35,[37][38][39]. A previous study also has shown that while exposure did not influence the fat bodies, characteristic changes were observed in the Malpighian tubules in G. mellonella larvae after infection [40].…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of secondary toxic metabolites such as azoxybenzene dicarboxylic acid and hydroxymethyl azoxybenzene in C. coronatus during culture growth were reported (106). However, their release during infection in insects and mammals has yet to be confirmed (23,106,107).…”
Section: Nutritional Requirements and Secreted Metabolitesmentioning
confidence: 99%
“…They need a traumatic lesion on the host's skin to attach their conidia and for the formation of a germ tube to penetrate the infected tissue using lipolytic and proteolytic enzymes. In fact, the expression of these types of enzymes in cultures of entomophthoralean species has been reported (12,102,106,107). Most of these enzymes have been found to play important roles in infected insects (11,76,99,107).…”
Section: Pathophysiologymentioning
confidence: 99%
“…mellonella is also a model host for human pathogens like Bacillus cereus [11], Candida albicans [12], Listeria monocytogenes [13] or Staphylococcus aureus [14]. This insect is also used in studies of entomopathogenic fungi [15][16][17]. Conidiobolus coronatus (Entomophthorales) is a soil fungus that is pathogenic to insects [18] and sometimes also to humans.…”
Section: Introductionmentioning
confidence: 99%